(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The writing skills are more important in English not only English but also improve your progress with reading. Reading exposes learners to different ideas and concepts. In addition, when you use some methods for improve Writing skills you can use some of the difficult tools to use correct sentence structures in writing. Writing in various formats – such as descriptive essays, persuasive articles, narratives, and reports. This will sharpen different writing skills.